Site index curves for Gmelina arborea Roxb - Greaves, A (Commenwealth Forestry Institute, University of Oxford, 1978)
The construction of the site index curves formed part of a wider-ranging study into the site and productivity relationships of Gmelina arborea Roxb. plantations in Nigeria (Greaves, 1973). The study area was located within the Derived Savanna zone (Keay, 1965) to the north-east of Benin City between latitudes 6anddeg; 35', and 7anddeg; 10' north and longitudes 6anddeg; 15' and 6anddeg; 40' east. The site studies entailed the establishment of 180 temporary sample plots of area 0.04 ha (0.1 ac), located to cover the full range of soils and topography encountered within the plantations. These plots also served as the data base for the site index curves.